HUBUNGAN MOTIVASI BELAJAR DAN HASIL BELAJAR KOGNITIF MELALUI PENGGUNAAN MEDIA VIRTUAL LAB OPHYSICS MATERI GELOMBANG CAHAYA DI KELAS XI SMA - Fauziah, Keyzi; Zulhelmi; M.Nor (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The learning process of Physics in Light Wave material requires an approach to visualization of abstract phenomena that must also pay attention to the affective aspects of students. Academic success in the use of technology such as the oPhysics virtual lab is strongly suspected to be closely related to students internal psychological drives. This study aims to analyze the significant relationship between the ARCS Model Learning Motivation (Attention, Relevance, Confidence, Satisfaction) and students Physics Cognitive Learning Outcomes through the use of virtual media of the oPhysics lab. This type of research is quantitative with an associative correlational design. The study involved a sample of 36 students of grade XI Science at Al-Huda High School Pekanbaru who were selected using the purposive sampling technique. Data were collected post-learning using the ARCS motivational questionnaire questionnaire and an objective test of cognitive learning outcomes (C1-C6) levels. Data analysis used the Pearson Product Moment correlation test and the determination coefficient based on SPSS software. The results showed a Significance value of , which means rejected and accepted. The value of the correlation coefficient was obtained , which indicates a positive relationship in the strong and unidirectional category. A determination coefficient value of confirms that ARCS learning motivation contributes significantly by to students' physical cognitive learning outcomes. In conclusion, the higher the ARCS motivation of students when exploring the virtual laboratory, the more optimal students cognitive thinking performance will be.